A clinical investigation of the relationship between the quality of conventional complete dentures and the patients' quality of life - Sara A. Alfadda; Hayam A. Al-Fallaj; Hajar A. Al-Banyan; Ruba M. Al-Kadhi (Elsevier, 2015)
Objective: The purpose of this study was to determine whether there is a correlation between the clinical quality of conventional complete dentures and patient quality of life. Materials and methods: This study included a random sample of 32 completely edentulous patients (15 males and 17 females) who were treated with conventional complete dentures. Using a validated questionnaire, three investigators evaluated the dentures independently on the basis of seven clinical parameters: esthetics (lip support and lower lip line), retention and stability of the maxillary and the mandibular dentures, and occlusion. Patients completed the validated Oral Health Impact Profile-20 (OHIP-20) questionnaire. Correlations were determined by using the point-biserial correlation coefficient. Results: Clinicians rated the overall clinical quality of the dentures satisfactory in 80.3% of patients. The mean (±standard deviation) total OHIP-20 score was 56.3 ± 15.9 out of a possible 120 maximum. A statistically significant negative correlation was found between the stability of the maxillary and mandibular dentures and the total OHIP-20 score (p = 0.009 and 0.0023, respectively). A negative correlation between the total OHIP-20 score and the retention of the mandibular denture approached significance (p = 0.092). Esthetics, retention of the maxillary denture, and occlusion were not correlated with patient quality of life (p > 0.169). Conclusion: Stability of the maxillary and mandibular dentures is the denture quality parameter that can most significantly affect patient quality of life. Keywords: Quality of life, Complete dentures